Penerapan Rasio Sampling Dalam Pendugaan Rasio Lahan Kritis di Wilayah Das Jratun - Iwa Sungkawa (ComTech: Computer, Mathematics and Engineering Applications, 2012)
This study aims to examine the application of ratio estimators on a sampling method by taking the case of estimating the ratio of critical land of every county around Jratun watershed. Through the estimation, a general description of critical land deployment for each region (county) can be obtained. In addition, the estimator of hose/interval is also determined for the ratio with the real level of 0.05. The simple random sampling method is used in conducting the estimation of ratio of the critical land to the total land area. Theestimation results show that the ratio of the critical land to the total area for 19 districts reaches 23.72%.